Comparison of non-catalytic and in-situ catalytic pyrolysis of Melia azedarach sawdust - Agnihotri N.; Mondal M.K. (My University, 2025)
This study focused on the in-situ catalytic pyrolysis of Melia azedarach sawdust by impregnating it with copper (Cu). Native and Cu impregnated Melia azedarach sawdust (MAS-N and MAS-C, respectively) were subjected to pyrolysis. MAS-N and MAS-C were characterized using proximate, ultimate and HHV analysis. Thermal degradation performance of MAS-N and MAS-C were examined by thermogravimetric analysis. Similar shapes of thermogravimetric curves indicated that Cu metal did not alter degradation pathway but lowered decomposition temperature and higher reaction rates were noticed for MAS-C due to catalytic effect of Cu. Optimization of operating process parameters was done by varying temperature, sweeping gas flow rate, particle size, packed bed height, pyrolysis time and heating rate for MAS-N. Maximum bio-oil yield for MAS-N was obtained at 550 ℃ temperature, 150 mL/min nitrogen flow rate, 8.4 cm bed height, 0.18–0.29 mm sized particles, 20 ℃/min heating rate and 60 min pyrolysis time. Further, effect of variation in temperature and catalyst to biomass ratio was studied for MAS-C and maximum bio-oil yield for MAS-C was obtained at lower temperature than that for MAS-N. Results were compared for catalytic and non-catalytic pyrolysis products via various characterization methods. Bio-oil properties were analysed by FTIR, GC-MS and 13C NMR. Proximate, ultimate, HHV, FTIR, XRD, SEM and BET surface area analysis were used to characterize properties of bio-char. Results suggested that Cu has catalytic effect on pyrolysis products. This article will be useful for promoting future research related to using heavy metal contaminated biomass as potential opportunities. © 2023